Adversus Calumniatores Medii Aevi. How the Middle Ages Paved Way for Modern Age - Gensler, Marek; Gralińska-Toborek, Agnieszka; Kazimierska-Jerzyk, Wioletta; Kędziora, Krzysztof; Miksa, Joanna (Practica et Speculativa: Studies Offered to Professor Andrzej M. Kaniowski, 2022)
The popular opinion sees Middle Ages as a “bad” period holding that it was a time of regress in civilisation and was characterized by exaggerated interest in religious and theological issues leading to a neglect of all other aspects of human existence. The two claims are refuted with arguments taken from the history of civilisation and science, as well as from history of political doctrines and history of universities.